1998
DOI: 10.1159/000013802
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and Event-Related Activity of the Auditory Cortex

Abstract: A neuromagnetic study in tinnitus patients and normal-hearing controls was performed with a modified contingent negative variation (CNV) paradigm. While the warning stimulus S1 was a tone burst at an intensity well above threshold, the imperative stimulus S2 was presented at a near threshold intensity because, in the majority of cases, the perceived loudness of tinnitus is very close to the threshold for a pure tone of the same frequency. Subjects had to respond to S2 by pressing a button until its offset was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 75 publications
1
8
0
2
Order By: Relevance
“…Consequently, the amplitude ratio of the P2m/N1m complex was smaller in tinnitus compared to controls. In a repeat study, the authors confirmed their earlier results and found that the P2m/N1m complex was smaller in tinnitus (114). A case report by Pantev et al (115) of a tinnitus patient who suffered acoustic trauma, showed the gradual recovery of the N1m/p2m complex to normal levels over 6 months, which correlated with steady recovery from tinnitus.…”
Section: Evaluation Of Tinnitus Abnormality Based On the Evoked Responsesupporting
confidence: 74%
“…Consequently, the amplitude ratio of the P2m/N1m complex was smaller in tinnitus compared to controls. In a repeat study, the authors confirmed their earlier results and found that the P2m/N1m complex was smaller in tinnitus (114). A case report by Pantev et al (115) of a tinnitus patient who suffered acoustic trauma, showed the gradual recovery of the N1m/p2m complex to normal levels over 6 months, which correlated with steady recovery from tinnitus.…”
Section: Evaluation Of Tinnitus Abnormality Based On the Evoked Responsesupporting
confidence: 74%
“…[13][14][15] Using MEG, Diesch and colleagues recently demonstrated that responses to the super-position of three amplitude-modulated tones were reduced in healthy controls (indicative of reciprocal inhibition), but increased in patients with tinnitus (indicative of abnormal reciprocal facilitation). This finding is compatible with the interpretation that tinnitus is associated with a reduced lateral or surround inhibition compared to control subjects.…”
Section: Increased Stimulus-induced Activitymentioning
confidence: 99%
“…This finding is compatible with the interpretation that tinnitus is associated with a reduced lateral or surround inhibition compared to control subjects. Similarly, a number of early studies reported abnormally enhanced transient N1 (N1m) responses to a 1-kHz tone in a group of tinnitus patients, [13][14][15] although these studies have not always been replicated. [16][17][18] One might expect such hyperexcitability to be greatest at frequencies corresponding to the tinnitus pitch and/or to the region of hearing loss.…”
Section: Increased Stimulus-induced Activitymentioning
confidence: 99%
“…Andere Autoren berichten über Veränderungen der späten, kortikalen akustisch evozierten Potentiale bei Patienten mit Tinnitus [9,10,23]. Unter Stimulierung des Hörsystems mit bestimmten Ton-Bursts gelang mit Hilfe von Magnetenzephalographien bei einigen Tinnituspatienten der Nachweis von veränderten Potentialen im Vergleich zu Normalpersonen [11].…”
Section: Erfolge Des Neurofeedback Bei Tinnitusunclassified